STRUCTURE OF THE UPPER LITHOSPHERE IN NORTHERN SIBERIA NEAR THE YENISEY RIVER - Grinson A.S. (My University, 1989)
The crust and upper mantle in northern Siberia near the Yenisey River were studied on the Dikson-Khilok profile of deep seismic sounding. Geologic and geophysical interpretation of all available data allowed us to map the section of the upper lithosphere in this region and distinguish its three structurally different types. Tectonic features of these Siberian paleorift structures seem to determine their specific metallogeny - copper-nickel in the Igarka-Noril'sk and kimberlite in the Yenissey - thereby confirming the fundamental concept that all such endogene ore deposits are formed in an environment of crustal extension in the cratonic stages, i.e., in rift zones.